Evaluation of microbial water quality in recreational area in Kuching area - Nadira, Binti Azuar (Universiti Malaysia Sarawak, UNIMAS, 2013)
This study was carried out to monitor microbiological water quality in two different recreational areas around Kuching area. Rachan waterfall and UNIMAS lake were chosen to determine the presence of indicator microorganisms such as Escherichia coli. Most probable number (MPN) was evaluated for detecting and enumerating E.coli in water samples. Temperature and pH were used as parameters to evaluate the correlation towards distribution of coliforms in water samples. The positive tubes were cultured on eosin methylene blue agar (EMBA) for detection of E.coli. A total of 30 isolates of E.coli were isolated from both recreational areas. The representative isolates were tested through gram staining and standard biochemical tests. Out of 30, 26 were confirmed as E.coli based on the morphological characteristics. The isolates were tested for the presence of pathogenic Escherichia coli O157:H7 strain by multiplex PCR method targeting the stx1and stx2 genes. The stx1 and stx2 genes were not detected in any of the E.coli isolates. This study showed that there are no pathogenic strains found in these recreational areas and it safe for human to do recreational activity.